Need Analysis of English for Specific Purpose:An Intensive English Course for Maritime Students - Setiawan, Iwan (IKIP Siliwangi, 2026)
As maritime students, English becomes an important language in communication especially for conducting international ships. This research is aimed to investigate the need analysis of ESP consists the necessities, lacks, and wants of maritime students. This research used a qualitative approach and descriptive design. The subjects of this research are nineteen maritime students who studied English in Kampung Inggris Pare – Kediri and they are from different institute and university. The researcher used questionnaire to get data of the need analysis. The finding shown that most of the students are in beginner level. It means that the students have little English proficiency. Besides, the analysis of the necessities revealed that not only speaking skill that students need but also listening skill and grammar, vocabulary, and pronunciation are necessary for them to communicate in their sailing. On the other hands, the students answered that communication skill become their lack due to having little or no English language knowledge. Moreover, the result of want analysis, shown that the students want several learning strategy that gives more speaking practice and learning material which consists of grammar for speaking, pronunciation, and vocabulary related to their needs to communicate in workplace.